PTU-127 The Macrogol MRI Challenge Test: A Novel Non Invasive Colonic Function Test. (4th June 2013) - Lam, C; Chaddock, G; Hoad, C; Costigan, C; Cox, E; Pritchard, S; Marciani, L; Gowland, P; Spiller, R
Abstract : Introduction: Managing resistant constipation commonly involves multiple often unpleasant invasive tests. Our aim was to develop a more acceptable non-invasive colonic function test. Methods: 13 patients (ages 21–60, female: male = 12:1) with chronic constipation (CC) unresponsive to simple laxatives; 9 with slow transit constipation, 2 obstructive defecation and 2 IBS with constipation. Whole gut transit (WGT) was assessed by ingesting 5 pills filled with Gadolinium-DOTA solution, 24 hours before study day when a fasting MRI scan of the abdomen was performed. Transit of the pills was assessed from an average weighted Transit Score (TS) previously shown to correlate well with the standard radio-opaque marker method (1). This enabled TS to be converted to WGT time in hours. Patients then ingested 1 litre of macrogol (MCG), followed by hourly MRI scans for 4 hours while they scored bowel symptoms from 0–10 (none – severe). Colonic movements were assessed using a motility index (integral of the duration of contraction in secs/2 minute X multiplied by the number of sections of the ascending colon showing contraction). Results were compared with values from 11 healthy volunteers (HV) previously reported (2). Results: (Mean±SEM) WGT time was calculated from the TS to be significantly greater for CC being 83 ± 12 hr vs. 30 ± 4 hr for HV (p < 0.01). The average fasting small bowel water content (SBWC) was increased for CC being 200 ± 18 compared to 51 ± 7ml in HV (p < 0.01). Fasting AC volumes were also greater in CC being 307 ± 26 compared to 205 ± 14ml in HV (p < 0.01). The average arrival time of MCG to the ascending colon (AC) was 74 ± 7 min in CC and 65 ± 5 in HV (p = 0.39). Motility index 2 hours after MCG ingestion was reduced in CC compared to HV being 14 ± 14 and 82 ± 14 (p = 0.04). Distension of the colon at 2 hours by MCG was greater for CC with AC volume of 615 ± 59 vs. 357 ± 46 ml in HV (p < 0.01). Time to first bowel movement after ingestion of MCG was delayed for CC compared to HV at 414 ± 144 and 117 ± 21 min (p = 0.04). Stool frequency for CC on the day of MCG ingestion were reduced compared to HV being 4.5 ± 1.4 versus 8.9 ± 1.2 (p < 0.01). Bloating score following ingestion of MCG was greater in CC being 2.3 ± 0.3 compared to HV 0.9 ± 0.3 (p = 0.02). Conclusion: CC patients have increased fasting SBWC and AC volumes compared to HV. When challenged with MCG, they showed greater distension and more discomfort with reduced motility and delayed bowel movement response. This MRI monitored MCG challenge test gives data on transit, sensory and motor function. Disclosure of Interest: None Declared References: Lam et al. BSG 2013 submission. Garsed et al. Gastroenterology 2012; 142:S814S.